Understanding the emerging Chinese working holiday market. (January 2021) - Fang, Yao; Chien, P Monica; Walters, Gabrielle
Working holidays have become a fast-growing phenomenon in China, yet research pertaining to this segment is scarce. This study explores the travel motivations, expectations and satisfaction Chinese Working Holiday Makers (WHMs) experienced with respect to their working holiday experiences in Australia. Fifteen interviews were conducted with Chinese WHMs pursuing a variety of work placements. Four key motivations and five important destination attributes were revealed along with a number of satisfaction determinants. Practical solutions for destination marketers as to how to reach and appeal to this viable market segment and improve the working holiday experience for Chinese youth are provided.